"Political Justice" in the Making: Otto Kirchheimer and His Late Work in Historical Perspective. (1st September 2016) - Hackler, Ruben; Herrmann, Lucia
Abstract : Since the publication of Otto Kirchheimer's late study Political Justice: The Use of Legal Procedure for Political Ends (1961) scholars have repeatedly debated the assessment of this text. The various readings of Political Justice can be explained by the way in which the study's subject and the author were historically situated. Our article provides insights into the author's biographical background as well as the intellectual and institutional processes in the USA and in Europe, which influenced the writing of the book. We outline key aspects of his understanding of political justice, which deals with the difference between class justice and political justice and with the possibilities and limits of actual political maneuvering within various forms of legal procedures. Viewed from today's perspective, Kirchheimer's analysis remains strikingly pertinent. The findings presented here aim to facilitate a renewed reading of Political Justice, inviting researchers to take Kirchheimer's research into consideration for the study of current ties between law and politics.